2003
DOI: 10.1590/s1676-24442003000300012
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine reduces myocardial tissue damage in rats submitted to chronic inhibition of systemic nitric oxide synthesis during 4, 14 and 28 days

Abstract: y key words unitermos abstractThe aim of the present work was to develop a qualitative chronopathological study concerning abnormalities in myocardium, due to nitric oxide (NO) blockage. We used 60 Wistar normotensive young male rats from several breeds. Groups of rats were submitted to L-Name (L) via oral administration dissolved in water (750mg/l) during days 4, 14 and 28. Other groups were submitted concomitantly to L-Name and hydralazine hydrocloride (L + H) (120mg/l). On days 4 and 14 (L group) we have fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…In the present work, using NO systemic blockage (L-NAME Model), we identified increase of vascular media, fibrotic scars, and perivascular fibrosis in left, right, and septal myocardium, similar to those lesions found by Hocher 26 in renovascular hypertension. Felix et al 16 , using infusion dose of aldosterone and angiotensin II in rats, found reactive and reparative fibrosis similar to those found in previous [5][6][7][8][9]18,19,22 and present works.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In the present work, using NO systemic blockage (L-NAME Model), we identified increase of vascular media, fibrotic scars, and perivascular fibrosis in left, right, and septal myocardium, similar to those lesions found by Hocher 26 in renovascular hypertension. Felix et al 16 , using infusion dose of aldosterone and angiotensin II in rats, found reactive and reparative fibrosis similar to those found in previous [5][6][7][8][9]18,19,22 and present works.…”
Section: Discussionsupporting
confidence: 88%
“…Nowadays, it has been discussed the degree of direct influence of NO -and the influence of hypertension produced by NO blockagein hypertrophy and cardiac lesions in the L-NAME model. Since the reduction of arterial hypertension in this model does not reduce significantly the hypertrophy and the lesions, these morbid processes are probably related to NO deficit 6 . Some studies showed that at least in some cases of hypertension, NO synthesis is reduced [10][11][12] .…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations